Left Atrial Appendage Volume As a New Predictor of Atrial Fibrillation Recurrence After Catheter Ablation - Teixeira, P (2018)
PURPOSE: Recurrence of atrial fibrillation (AF) after catheter ablation is common, being clinically relevant to identify predictors of recurrence. The left atrial appendage (LAA) role as an AF trigger is scarcely explored. Our aim was to identify if LAA volume is an independent predictor of AF recurrence after catheter ablation. METHODS: We analysed 52 patients (aged 54 ± 10 years, 58% male) with paroxysmal and persistent AF who underwent a first AF catheter ablation and had performed contrast-enhanced cardiac computed tomography (CT) prior to the procedure. RESULTS: The mean left atrial and LAA volumes measured by cardiac CT were 98.9 ± 31.8 and 9.3 ± 3.5 mL, respectively. All patients received successful pulmonary vein isolation and were followed up for 24 months. AF recurrence occurred in 17 patients (33%). LAA volume was significantly greater in patients with AF recurrence than in those without recurrence (11.3 ± 2.9 vs. 8.2 ± 3.4 mL; p = 0.002). Multivariable analysis using Cox regression revealed that LAA volume (hazard ratio 1.32; 95% confidence interval 1.12-1.55; p = 0.001) and persistent AF (hazard ratio 4.22; 95% confidence interval 1.48-12.07; p = 0.007) were independent predictors for AF recurrence. An LAA volume greater than 8.825 mL predicted AF recurrence with 94% sensitivity and 66% specificity. The Kaplan-Meier analysis showed a lower rate free from AF recurrence in the group with an LAA volume >8.825 mL (p < 0.001). CONCLUSIONS: Larger LAA volume was associated with AF recurrence after catheter ablation in patients with paroxysmal and persistent AF.